2001
DOI: 10.1046/j.1524-4725.2001.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tacrolimus in the Treatment of Bovine Collagen Hypersensitivity

Abstract: Topical tacrolimus may be a useful first-line or adjuvant therapy in the management of bovine collagen allergic reactions. Further clinical experience with its use for bovine collagen hypersensitivity is required to determine its true efficacy in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…14,15,28 Allergic reactions to bovine collagen may be treated with topical, intralesional, or a brief course of systemic corticosteroids, and there are also reports of patients who have been successfully treated with oral cyclosporine 33 or topical tacrolimus. 34,35 Zyderm I is used for correction of superficial wrinkles, whereas Zyderm II is more effective in moderate to deep wrinkles, and both of them should be injected in the superficial dermis. In contrast, Zyplast works best when placed at the mid-dermis and is more valuable in treating deeper lines, such as nasolabial folds, deep acne scars, and lip augmentation through injection in the vermillion border.…”
Section: Bovine Collagen Key Pointsmentioning
confidence: 99%
“…14,15,28 Allergic reactions to bovine collagen may be treated with topical, intralesional, or a brief course of systemic corticosteroids, and there are also reports of patients who have been successfully treated with oral cyclosporine 33 or topical tacrolimus. 34,35 Zyderm I is used for correction of superficial wrinkles, whereas Zyderm II is more effective in moderate to deep wrinkles, and both of them should be injected in the superficial dermis. In contrast, Zyplast works best when placed at the mid-dermis and is more valuable in treating deeper lines, such as nasolabial folds, deep acne scars, and lip augmentation through injection in the vermillion border.…”
Section: Bovine Collagen Key Pointsmentioning
confidence: 99%
“…A medium‐dose pulse therapy (e.g., 240 mg (60/60/40/40/20/20 mg) of methylprednisolone weekly) was performed in most participants. The interval was extended by approximately 1 week after each treatment cycle 13 . Sustained success is usually achieved after six treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen and colleagues 13,33 report beneficial effects for treatment of localized adverse reactions with tacrolimus (e.g., after collagen injection). Twice‐daily application for 3 to 6 weeks is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical, intralesional, or a brief course of systemic corticosteroids may be used to treat these reactions. It has been reported that allergic reaction to bovine collagen may be treated with oral cyclosporine (22) or topical tacrolimus (23).…”
Section: Bovine Collagen Implantsmentioning
confidence: 99%